2018
DOI: 10.1177/2058460118796539
|View full text |Cite
|
Sign up to set email alerts
|

Bone density measurements adjacent to acetabular cups in total hip arthroplasty using dual-energy CT: an in vivo reliability and agreement study

Abstract: BackgroundMeasuring bone mineral density (BMD) around acetabular prosthetic components with computed tomography (CT) is challenged by the complex anatomy and metal artifacts. Three-dimensional (3D) segmentation is required for the analysis, but it is usually not practically applicable on current CT workstationsPurposeTo test the between-scan agreement and reliability of custom segmentation software for BMD measurements adjacent to cemented and uncemented acetabular cups in dual-energy CT (DECT).Material and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Furthermore, the largest difference was found for the posterior quadrant which is consistent with our findings in the ischium. 27 Wilkinson et al 14 also investigated intra-operator variability of BMD measurements and calculated similar CoV values as those found in this study although this was using 2D ROIs. It was hypothesised that with an increasing number of implants in situ there would be decreased intra-and interoperative reliability.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, the largest difference was found for the posterior quadrant which is consistent with our findings in the ischium. 27 Wilkinson et al 14 also investigated intra-operator variability of BMD measurements and calculated similar CoV values as those found in this study although this was using 2D ROIs. It was hypothesised that with an increasing number of implants in situ there would be decreased intra-and interoperative reliability.…”
Section: Discussionsupporting
confidence: 75%
“…Although reported in mean BMD, Mussmann et al 27 found similar intra-operator reliability results (~0%-10% difference between measurements) when splitting the acetabulum. Furthermore, the largest difference was found for the posterior quadrant which is consistent with our findings in the ischium.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recently, there have been advancements in dual-energy monochromatic imaging CT, which has shown promising effects in periprosthetic imaging of hip arthroplasty when combined with metal artifact reduction software (32)(33)(34)(35). This technique may significantly improve the diagnostic accuracy of CT imaging for periprosthetic RLLs, compared to single energy CT scanning.…”
Section: Discussionmentioning
confidence: 99%
“…As already demonstrated in previous studies 10 , 18 , PMI datasets can improve image quality in terms of contrast and noise as well as reduce beam hardening artifacts depending on the energy selected for PMI generation compared to conventional 120 kVp SECT. For other applications such as a non-automatic and dedicated bone mineral segmentation, it has also been shown that the use of PMI datasets could reduce inter- and intra-observer variability 31 . However, to fulfill the requirements of the as-low-as-reasonably-achievable (ALARA) principle, only DECT scans were clinically acquired for the investigated patient cohort, since no added value for medical purposes was expected from a conventional 120 kVp SECT and an 80/140 kVp DECT scan in direct succession.…”
Section: Discussionmentioning
confidence: 99%